The extent of the availability of political concepts in the content of history books for the preparatory stage (Journal of the College of Basic Education, 2025)
The study aimed to identify the political concepts included in the content of history books for the preparatory stage, and to achieve the goal of the research, the researcher adopted the descriptive approach of the type of content analysis as a research objective, and the idea (theme) as a unit for recording and repetition as a unit for a number of experts and to ensure its validity. In newspapers, measurement and evaluation, and in order to verify, and urge to verify the accuracy of numbers, and analysis through teaching, teaching, and analysis passers-by on a group of experts in newspapers, measurement and evaluation, in order to ensure the assimilation of political policy in history books for the preparatory stage. Re-analysis, by agreement coefficient using the Holsti equation H.listi.The results of the research resulted in the availability of political concepts in history books in the preparatory stage, where the number of concepts reached (4330) concepts, and the concept of war came in the first place with a frequency of (340) and at a rate of 7.90%, and in the second place was the concept of revolution with a frequency of (288) and at a rate of 6.65%, and in the third place was the concept of revolution Al-Watan with a frequency of (276) 6.60%, which indicates a good political concepts from here, while some of the concepts of the sovereign, and note, and note, and note, and note, and note, and note, and note, and note check in some books Such as (statelet, fragmentation, keratin).In light of the results of the research, the researcher indicated to a number of your region that the plans for writing books should be reviewed by the Ministry of Education.He suggested a number of proposals that include an empirical study to determine the extent to which students acquire political concepts in the preparatory stage.